Pemberdayaan Masyarakat Dalam Pelayanan Rehabilitasi Mental Spiritual Peserta Didik Pasca Pandemi Covid-19 Oleh Dinas Kesehatan Provinsi Riau - Haikal Mulki; Setyo Utomo (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
Students mental health in the post-Covid-19 pandemic period has become an increasingly important issue due to the rising risk of psychological disorders, while mental health and rehabilitation services continue to face various challenges, including a shortage of professional personnel, limited outreach efforts, and unequal access to available services. This study aims to analyze the implementation of mental rehabilitation and mental health service programs for students administered by the Riau Provincial Health Office and to identify the supporting and inhibiting factors affecting their implementation. This research employed a qualitative method using a literature review approach. The study utilized secondary data obtained from official documents, reports, policies, and publications issued by the Riau Provincial Health Office, as well as relevant academic literature. Data were analyzed using a descriptive analysis technique to describe program implementation, assess its effectiveness, and identify the barriers and supporting factors influencing the success of mental rehabilitation and mental health programs for students in the post-pandemic period. The findings indicate that mental health services for students have been implemented through various rehabilitation and mental health education programs; however, their effectiveness remains suboptimal due to limited professional human resources, inadequate public outreach, and unequal service accessibility. On the other hand, the utilization of digital technology, improvement of mental health literacy, and strengthened cross-sector collaboration represent strategic factors with significant potential to enhance accessibility, service quality, and the effectiveness of mental rehabilitation. Therefore, strengthening interagency partnerships and developing integrated, systematic, and sustainable mental health programs are essential to support students' psychological recovery and well-being in the post-pandemic era.